Adjustment of the dinar exchange rate policy to macroeconomic challenges of the national economy : DOI: 10.5937/etp2404063S - Sekulić, Aleksandar; Beker Pucar, Emilija; Stojkov, Stefan (Ekonomija - teorija i praksa, 2025)
This paper analyzes the choices and changes in exchange rate policy in the Republic of Serbia in response to key macroeconomic challenges since the political and economic changes of 2000. The dinar exchange rate was initially pegged to the Euro from 2000 to 2009, a period that can be divided into two subperiods: the phase of macroeconomic stabilization from 2000 to 2003, during which the exchange rate served as a nominal anchor, and the phase of soft pegging from 2003 to 2009, responding to the deteriorating competitiveness of the national economy. After the exchange rate was pegged, the national currency shifted to a managed-floating regime, and monetary authorities adopted inflation targeting from 2009 to 2023. The era of managed floating can be analyzed in two subperiods: de jure and de facto managed floating from 2009 to 2017, and the 'fear of floating' period from 2017 to 2023, marked by the distinction between de jure (managed floating) and de facto (stable exchange rate) exchange rate regimes. The exchange rate policy of national monetary authorities has been adjusted to address urgent macroeconomic challenges, primarily the fight against inflationary pressures (exchange rate as a nominal anchor), the need to boost exports, economic growth, and the external position (exchange rate as a competitiveness stimulus), and the need to prevent financial destabilization of the national economy (exchange rate as a guarantee of financial stability).